2015
DOI: 10.4236/as.2015.63037
|View full text |Cite
|
Sign up to set email alerts
|

Ornamental Bee Plants as Foraging Resources for Urban Bees in Southern Brazil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…More research is needed to evaluate the effectiveness of pollinator seed mixes (Garbuzov & Ratnieks 2014). However, bees and other insect pollinators benefit from both native and nonnative plants (e.g., Matteson & Langellotto 2011;Hanley et al 2014;Pardee & Philpott 2014;da Silva Mouga et al 2015), although for managerial purposes natives are preferred (Williams et al 2011). Other underexplored topics include social dimensions of self-organizing neighbors who transform lawns (and their affiliated cultural models) to attract bees and butterflies for conservation (van Heezik et al 2012) and the effectiveness of different citizen conservation activities (Asah & Blahna 2013).…”
Section: Abstract: Research On Urban Insect Pollinators Is Changing Vmentioning
confidence: 99%
“…More research is needed to evaluate the effectiveness of pollinator seed mixes (Garbuzov & Ratnieks 2014). However, bees and other insect pollinators benefit from both native and nonnative plants (e.g., Matteson & Langellotto 2011;Hanley et al 2014;Pardee & Philpott 2014;da Silva Mouga et al 2015), although for managerial purposes natives are preferred (Williams et al 2011). Other underexplored topics include social dimensions of self-organizing neighbors who transform lawns (and their affiliated cultural models) to attract bees and butterflies for conservation (van Heezik et al 2012) and the effectiveness of different citizen conservation activities (Asah & Blahna 2013).…”
Section: Abstract: Research On Urban Insect Pollinators Is Changing Vmentioning
confidence: 99%
“…Many studies have reported lists of plant taxa visited by bees in urban areas (e.g. Matteson and Langellotto 2011;da Silva Mouga et al 2015;Mach and Potter 2018;Rollings and Goulson 2019;Prendergast and Ollerton 2021), although few report the proportion of the available plant species that was used by bees. Although a large diversity of flowering plants was available to bees at these urban sites, they were recorded visiting only about 26% of the plant taxa on average during the surveys.…”
Section: Resource Utilisation By Speciesmentioning
confidence: 99%
“…Urban gardens often comprise a large variety of exotic and alien plants in the United Kingdom (Smith et al 2006;Rollings and Goulson 2019) and each garden provides relatively different resources. These resources may enhance the diversity of bees and support a wide array of species (da Silva Mouga et al 2015;Lowenstein et al 2019).…”
Section: Resource Utilisation By Speciesmentioning
confidence: 99%
“…Ornamental plants are recognized for their plastic characteristics (flowers, perfume, fruits, stem) and are strategically grown, usually for decorative purposes, and used as aesthetic adornments (CASTRO, 2014). Ornamental plants are included in all taxonomic divisions, among which the families Euphorbiaceae, Lamiaceae, Solanaceae, Verbenaceae and Rosaceae stand out (MOUGA et al, 2015). Their trade is well developed, making commercial issues often stand out in relation to ecological and environmental problems (TOSCANO et al, 2019).…”
Section: Introductionmentioning
confidence: 99%

Palynological characterization of ornamental plants

Helen Sabrine Hoffmann,
Denise Monique Dubet da Silva Mouga
2023
ABC